Recent Publications (Quarterly Journal of Economics, 1953)
Recent Publications Get access The Quarterly Journal of Economics, Volume 67, Issue 2, May 1953, Pages 306–310, https://doi.org/10.1093/qje/67.2.306 Published: 01 May 1953